To find the value of the expression \( 3w \cdot 2 - 3w + 8 \) when \( w = 4 \), we can substitute \( w \) with \( 4 \):
-
Substitute \( w \) into the expression: \[ 3(4) \cdot 2 - 3(4) + 8 \]
-
Calculate \( 3(4) \): \[ 3(4) = 12 \]
-
Now substitute this back into the expression: \[ 12 \cdot 2 - 12 + 8 \]
-
Next, calculate \( 12 \cdot 2 \): \[ 12 \cdot 2 = 24 \]
-
Now substitute this value back into the expression: \[ 24 - 12 + 8 \]
-
Now do the subtraction and addition from left to right:
- First, \( 24 - 12 = 12 \)
- Then, \( 12 + 8 = 20 \)
Thus, the value of the expression when \( w = 4 \) is \( \boxed{20} \).